'Bottoms up': A case study on integrating public engagement within a university culture. (21st September 2021) - Ní Shúilleabháin, Aoibhinn; McAuliffe, Fergus; Ní Shé, Éidín
Abstract : page_366 other This study tracks the integration of public engagement within the systems, structures and culture of a university in Ireland. Public engagement, as an activity of research institutes, is gaining increased attention from policy and funding sources across Europe. However, little has been heard on the processes and practices which bring public engagement to the fore of conversations and activities in such institutions. In this practice case study, we track the evolution of a community of practice of public engagement in an Irish university over three years, through a bottom-up approach taken by a small group of faculty and staff, and organized through collective leadership to maintain momentum over the time period. With the support of key leadership figures, who provided top-down financial and structural support, we trace the narrative of defining public engagement within the university through stakeholder workshops, recording relevant activities with an institution-wide census, updating university public engagement reporting metrics, and establishing an active community of practice. Four key learnings are identified from this collective narrative: (1) the need for patience in attempting to instigate change within an institution; (2) the importance of establishing a shared understanding; (3) the importance of enacting collective leadership as a community; and (4) the necessity of leadership support with grass-roots activity. Reflection on these learnings suggests that the embedding of public engagement in institutions requires both personal and institutional investment.